Criteria of institutional selection, service quality, adjustment and satisfaction among international postgraduate students - Hosseini, Narges (2013)
Increasing trends of students going abroad for further studies in the last two decades has motivated higher education institutions to find the criteria of institutional selection of international students, improve the service quality of education and reduce the adjustment problems of these students to keep them satisfied. Malaysia is one of the countries which always try to achieve high academic standards in the education system to reach the global market. For this purpose, this study used two sets of quantitative questionnaire and distributed them among two groups of international postgraduate students in Universiti Teknologi Malaysia (UTM). The first questionnaire is SERVQUAL, Adjustment and Satisfaction (SAS) questionnaire which was distributed among 353 respondents in UTM. Four dimensions of service quality namely tangible, consistency, assurance and compassion were obtained. Furthermore, high level of adjustment and low level of service quality and satisfaction from the respondents’ perspective were observed. In addition, the study represented the relationship and differences in these based on demography. The second instrument is Analytical Hierarchy Process (AHP) Questionnaire which was distributed to 30 international postgraduate students in UTM. AHP findings indicated that “Academic Qualification” is the most satisfactory criterion of institutional selection while “Study Abroad” is the lowest. Additionally, this study was able to show that international postgraduate students in UTM have negative perceptions of education service quality in this university. In the case of UTM, international postgraduate students tend to compare UTM with the education in academic universities of US, UK, Australia and Europe as the standard and general class for higher education and they may also compare the fees with service quality in UTM.